1991
DOI: 10.1063/1.349332
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative model for an interaction between extended dislocation loops and impurities in Czochralski silicon based upon the photoluminescence analysis

Abstract: D-line luminescence at the photon energies of 0.81 and 0.87 eV in Czochralski silicon containing extended dislocation loops has been characterized. In samples containing a high-oxygen concentration and in tin-doped samples, the D-line luminescence was observed. In contrast, no D-line luminescence was detected in samples containing a low-oxygen concentration, except when the sample was deliberately contaminated with Cu. The results clearly indicate that the optical centers responsible for the D-line luminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Wijaranakula has performed a systematic study of the oxygen precipitation behavior in Sn-and C-doped p-type CZ silicon in the temperature range 400-900°C. 7,16,17 The results are summarized in Fig. 3a and b, representing the loss of interstitial oxygen as determined by FTIR after a single-step isochronal anneal for 100 h in a nitrogen atmosphere and the bulk defect density after preferential etching of samples which underwent a 100 h nucleation anneal in N 2 at the indicated temperature followed by a fixed growth step at 1050°C for 50 h, respectively.…”
Section: Impact Of Tin On the Diffusion And Aggregation Of Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…Wijaranakula has performed a systematic study of the oxygen precipitation behavior in Sn-and C-doped p-type CZ silicon in the temperature range 400-900°C. 7,16,17 The results are summarized in Fig. 3a and b, representing the loss of interstitial oxygen as determined by FTIR after a single-step isochronal anneal for 100 h in a nitrogen atmosphere and the bulk defect density after preferential etching of samples which underwent a 100 h nucleation anneal in N 2 at the indicated temperature followed by a fixed growth step at 1050°C for 50 h, respectively.…”
Section: Impact Of Tin On the Diffusion And Aggregation Of Oxygenmentioning
confidence: 99%
“…In the latter case, a detection limit of ϳ1.8 ϫ 10 16 atom/cm 3 for the 120 Sn isotope is quoted in the literature. 7 That Sn is at the same time isoelectronic and a selective vacancy trap is interesting from a perspective of impurity-diffusion 8 and aggregation studies. First, the impact of the Fermi level or Coulombic interactions on impurity pairing can be studied by comparing Sn-free with Sn-doped material; in the latter case, only elastic interactions play a role.…”
mentioning
confidence: 99%
“…It was reported that the D1 and D2 lines originate from edge and screw dislocations, respectively. [19][20][21] The two lines were merged into the D a1 band at room temperature. 9) This supports the idea that the D a1 band has two kinds of polarization properties corresponding to the tilt and twist structures of SA-GBs.…”
mentioning
confidence: 99%
“…Furthermore, it has been determined that Sn improves [77] the minority carrier lifetime in Fe-contaminated Si, influences [78] the recombination characteristics of γ-irradiated Si, and accelerates [79] the degradation conductivity of electron irradiated Si. Sn doping has also been used to monitor [80] the interaction between extended dislocation loops and impurities in Cz-Si. It affects the diffusion of oxygen, as well as the formation of thermal donors and oxygen precipitates in Si [39,74,[81][82][83].…”
Section: Introductionmentioning
confidence: 99%